MASALAH–MASALAH YANG DIALAMI SISWA MTs N NAUMBAI KECAMATAN KAMPAR - Erni '; Tri Umari; Zulfan Saam (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: The research is aimed at 1) finding out personal problems of male and female students of Naumbai State Islamic Junior High School of Kampar Sub District; 2) finding out emotional problems of male and female students of Naumbai State Islamic Junior High School of Kampar Sub District; 3) finding out learning problems of male and female students of Naumbai State Islamic Junior High School of Kampar Sub District; 4) analising familial problems of male and female students of Naumbai State Islamic Junior High School of Kampar Sub District; 5) analising social problems of male and female students of Naumbai State Islamic Junior High School of Kampar Sub District; 6) analising the general description of male and female students’ problems of Naumbai State Islamic Junior High School of Kampar Sub District; 7) analising the category of male and female students' problems in general at Naumbai State Islamic Junior High School of Kampar Sub District . The data about problems faced by students were taken by using questionnaire. The population of the research were the entire students of Naumbai State Islamic Junior High School of Kampar Sub District from 7th and 9th grade which are amounted 200 persons. The sampling technique is the total sampling namely the entire members of the population become samples. The research results showed that: 1) the most dominant personal problems faced by male and female students were categorized as moderate; 2) the most dominant emotional problems faced by male and female students were categorized as moderate; 3) the most dominant learning problems faced by male and female students were categorized as low; 4) the most dominant familial problems faced by male and female students were categorized as low; 5) the most dominant social problems faced by male and female students were categorized as low; 6) as a general description, male and female students generally experienced more personal and social problems; 7) the problems of personal, emotional, learning, familial, and social aspects experienced by male and female students are generally categorized ‘low’.Keywords: Problems